Identification of Key Genes and Pathways in Post-traumatic Stress Disorder Using Microarray Analysis - Bian, Yaoyao; Yang, Lili; Zhao, Min; Li, Zhengjun; Xu, Yuying; Zhou, Guilian; Li, Wenlin; Zeng, Li (Frontiers in Psychology, 2019)
Background Post-traumatic stress disorder (PTSD) is characterized by impaired fear extinction, excessive anxiety and depression. However, the cause and potential molecular events of PTSD are not fully understand. Hence, the aim of this study was to identify key genes and pathway involved in PTSD and reveal underlying molecular mechanisms by using bioinformatics analysis. Methods The mRNA microarray expression profile dataset was retrieved and download from the Gene Expression Omnibus (GEO) database and the differentially expressed genes (DEGS) were identified. Gene function annotations and enrichment analysis were conducted by using Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway. Subsequently, Cytoscape software was used for protein-protein interaction (PPI) network and module analysis by the plugin MCODE. Finally, these key genes and pathway were verified in animal models by Real-Time quantitative (qRT-PCR). In addition, we performed text mining among the key genes and pathway with PTSD by using COREMINE. Results A total of 1004 DEGS were identified. Gene functional annotations and enrichment analyses indicated that the most associated pathway was the Wnt signaling pathway. Using PPI network and module analysis, we identified a various “seed” genes. These genes were further verified in animal models. In addition, text mining indicated that Cytochrome P450 Family 1 Subfamily A Member 2 (CYP1A2), Synaptotagmin 1 (SYT1), and Neuroligin 1 (NLGN1) were associated with the Wnt signaling pathway and PTSD. Conclusions By using bioinformatics analysis, we identified several genes and relevant pathways which may represent key mechanisms involved in the development of PTSD. However, these findings require verification in future experimental studies.